Preliminary Results of a RANS Simulation for a Floating Point Absorber Wave Energy System Under Extreme Wave Conditions - Yu, Y.; Li, Y. (National Renewable Energy Laboratory (U.S.), 2011)
This paper presents the results of a preliminary study on the hydrodynamics of a moored floating-point absorber (FPA) wave energy system under extreme wave conditions.